Feedback passivation plus tracking-error-based multivariable control for a class of free-radical polymerisation reactors - Nguyen, T. Sang; Hoang, Ngoc Ha; Hussain, Mohd Azlan (Taylor & Francis, 2019)
This paper proposes a tracking-error-based multivariable control to stabilise a nonlinear system at the desired trajectory (including the open-loop unstable equilibrium manifold). The control approach is developed on the basis of feedback passivation and then applied to stabilise globally exponentially a class of free-radical polymerisation reactors. More precisely, under certain conditions the system dynamics can be rendered strictly input/output passive through the use of an appropriate input coordinate transformation. A canonical form related to the so-called port-Hamiltonian representation of passive system is consequently derived and provides physical interpretations such as dissipative/non-dissipative term and supply rate. A feedback law based on tracking-error is then designed for the global exponential stabilisation at a reference trajectory passing through the desired set-point. The theoretical developments are illustrated for polystyrene production in a continuous stirred tank reactor. Numerical simulations show that the system trajectory converges globally exponentially to the reference trajectory despite effects of disturbance. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.